Meloxicam mitigated methylglyoxal-induced glycative stress in rats - Talha Fayyaz; Ghulam Abbas; Hammad Ahmed; Najeeb Khatian; Shumaila Usman; Uzair Nisar; Noor Ain; Yamna Khurshid; Syed Ali (Iranian Journal of Basic Medical Sciences)
Objective(s): Glycation is one of the primary underlying processes attributed to senescence and related diseases. No medicine currently targets this harmful manifestation. Drug repurposing is an efficient and cost-effective way of developing drugs. The present study evaluated meloxicam, a clinically used NSAID, for its ability to offer protection against glycative stress.Materials and Methods: Methylglyoxal (MGO; 17.25 mg/kg) was administered for two weeks to create a rat model of glycative stress. Aminoguanidine (AG; 50 mg/kg) and Meloxicam (MEL; 0.15, 0.3, and 0.6 mg/kg) were used as standard and test agents, respectively. Afterward, the cognitive (Morris Water Maze), liver (LFT), and kidney (Creatinine) functioning were evaluated. The expression of genes of interest (TNF-α, RAGE, BACE, Glyoxalase, and VEGF) were estimated (qPCR) in the liver, brain, and kidney along with histopathology (H&E staining). Carboxymethyllysine (CML) levels in rat plasma were evaluated via ELISA.Results: MEL treatment has significantly (P<0.05) protected the MGO-induced cognitive (duration in target quadrant, time taken to get to target quadrant, and the frequency of crossings via platform location), hepatic, and renal impairment. The qPCR data revealed that MEL prevented MGO-induced enhancement in the expression of genes of interest. Additionally, the CML levels were significantly (P<0.005) normalized by concomitant administration of MEL. Histopathological examination did not reveal any remarkable outcomes.Conclusion: MEL has significantly mitigated the rats’ MGO-induced cognitive, liver, and kidney impairments. Hence, it appears to be a potential molecule for repurposing as an antiglycation agent.